If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -9y = 12solvey Solving 6x + -9y = 12elosvy Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9y' to each side of the equation. 6x + -9y + 9y = 12elosvy + 9y Combine like terms: -9y + 9y = 0 6x + 0 = 12elosvy + 9y 6x = 12elosvy + 9y Divide each side by '6'. x = 2elosvy + 1.5y Simplifying x = 2elosvy + 1.5y
| 4(2-x)+2(1-5x)=5(2-3x)+x | | 6x^4-15x^6= | | 6x=7.20 | | 52-8= | | 9(n-15)-17n=-3-9(n+13) | | 21=-3p-6 | | b+9+2b=6 | | 3x+x-10=90 | | x-0.6=9.64 | | 3+12b+36a= | | 0-y=8 | | 2x+y=y+2x | | -2(-4x+3)=-6(-8-10x) | | 8x^2+46x-764=0 | | 5x+2x-30=180 | | -3(8+5x)=-84 | | 6x=10x-32 | | 2x^2+7x-22=0 | | 5-6(7a-5)=287 | | 12k^2-8k= | | -5(7p+2)=4p+9 | | 2x+45=7x+5 | | -6-8m=10-2m-8m | | 4+t=-16 | | (3*4)*7=3*(4*7) | | 0=-16t^2+13t+16 | | 4e^8t=6e^7t | | p+6=10 | | 3-4t=-3(t-1) | | 6x-32=3y-8 | | 6(4+3x)=132 | | 8x=10x-30 |